2014
DOI: 10.2139/ssrn.2518460
|View full text |Cite
|
Sign up to set email alerts
|

Supply-Side Barriers to Cross-Border E-Commerce in the EU Digital Single Market

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…However, this does not automatically imply that the existing divide in the use of other digital technologies will follow a similar trend. Our results further emphasize the role played by country specific cultural (e.g., see Gomez-Herrera et al, 2014, for evidence on the role played by language as a barrier to cross-border e-commerce), institutional and regulatory frameworks as factors that shape the potential for the closing of the digital divide, confirming the conclusions that have been drawn by other studies such as Cardona and Martens (2014) and Coad and Duch-Brown (2017). While the scenario design of our projections is arguably a simple benchmark, the method proposed in this study in principle allows for the creation of scenarios based on different developments of the socioeconomic covariates, which can help compare different policy paths aimed at achieving a fully integrated digital single market.…”
Section: The Digital Divide and Convergence Trends: A Projection Exercisesupporting
confidence: 89%
“…However, this does not automatically imply that the existing divide in the use of other digital technologies will follow a similar trend. Our results further emphasize the role played by country specific cultural (e.g., see Gomez-Herrera et al, 2014, for evidence on the role played by language as a barrier to cross-border e-commerce), institutional and regulatory frameworks as factors that shape the potential for the closing of the digital divide, confirming the conclusions that have been drawn by other studies such as Cardona and Martens (2014) and Coad and Duch-Brown (2017). While the scenario design of our projections is arguably a simple benchmark, the method proposed in this study in principle allows for the creation of scenarios based on different developments of the socioeconomic covariates, which can help compare different policy paths aimed at achieving a fully integrated digital single market.…”
Section: The Digital Divide and Convergence Trends: A Projection Exercisesupporting
confidence: 89%
“…The Mystery Shopping Survey demonstrated that electronic goods are most likely to be subject to geo-blocking. An earlier 2009 Mystery Shopping survey had already come to similar conclusions (Cardona & Martens, 2014). These results validate the decision to use electronic goods as a benchmark for the geo-blocking impact simulations.…”
supporting
confidence: 64%
“…More and more traditional enterprises have started to enter the industry, fully driving the rapid growth of the economic index [2][3][4]. According to statistics, just in 2018, the overall transaction scale of cross-border e-commerce in China reached an astonishing 4.3 trillion yuan, with a year-on-year growth of 37%, and the transaction volume of imported e-commerce also reached 723.7 billion yuan [5].…”
Section: The Introductionmentioning
confidence: 99%